2020
DOI: 10.1101/2020.01.24.917922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Anorectal Function Measured using Wearable Digital Manometry and a High Resolution Manometry System

Abstract: 17There is a need for a lower cost manometry system for assessing anorectal function in 18 primary and secondary care settings. We developed an index finger-based system (termed 19 "digital manometry") and tested it in healthy volunteers, patients with chronic 20 constipation, and fecal incontinence. Anorectal pressures were measured in 16 21 participants with the digital manometry system and a 23-channel high-resolution 22 36

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As this probe did not comply with the anorectal angle, greater force might be encountered due to the higher tissue contact stress (force per unit area), where the body of the probe is forced against the anorectal angle as well as the sphincters, rather than just measuring fluid pressure within the anus or rectum [14]. This hypothesis may be supported by the results of the study by Attari et al [21], who compared HRM to wearable pressure sensors mounted on a glove (digital manometry, DM) and found that the HRM catheter recorded higher pressures than the DM sensors. A possible explanation for lower pressures recorded by DM is that the finger can adapt to the anorectal angle and potentially avoid the tissue stress encountered by the stiffer standard probe.…”
Section: Discussionmentioning
confidence: 93%
“…As this probe did not comply with the anorectal angle, greater force might be encountered due to the higher tissue contact stress (force per unit area), where the body of the probe is forced against the anorectal angle as well as the sphincters, rather than just measuring fluid pressure within the anus or rectum [14]. This hypothesis may be supported by the results of the study by Attari et al [21], who compared HRM to wearable pressure sensors mounted on a glove (digital manometry, DM) and found that the HRM catheter recorded higher pressures than the DM sensors. A possible explanation for lower pressures recorded by DM is that the finger can adapt to the anorectal angle and potentially avoid the tissue stress encountered by the stiffer standard probe.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that the intrarectal pressure measured using high-resolution manometry is 80 mm Hg during simulated defecation and up to 200 mm Hg during squeezing. 20,21 In addition, the peak intrarectal pressure is higher in males than in females, which might contribute to male sex being a reported risk factor for AL. much higher than the anastomotic bursting pressure in our porcine model, the anastomotic bursting pressure in patients who undergo low anterior resection reportedly becomes much higher at 3-6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The HR-ARM catheter con guration consists of ve pressure sensors in the anal canal spaced 10 mm apart, two sensors on the distal end used to measure rectum pressure and balloon in ation, and one external reference sensor outside the body to assess atmospheric pressure. 9 The internal anal sphincter is a circular, smooth muscle innervated via the sacral nerves responsible for ensuring the anal canal closure at rest. 10 During the rst stage of the evacuation of feces, migrating contractions propel the colonic contents into the rectum.…”
Section: Introductionmentioning
confidence: 99%